2014
DOI: 10.1016/j.jssc.2014.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal nitridation kinetics of TiSi2 powders

Abstract: The aim the present work is to determine the reaction kinetics between a TiSi 2 powder with gaseous nitrogen. Isothermal nitridation of TiSi 2 powders with fine (1.4µm) and medium (4.5µm) particle size has been studied in pure nitrogen atmosphere ranging from 1000 to 1200°C for duration up to 50 hours. The isothermal nitridation kinetics of TiSi 2 powders were investigated by thermogravimetry. The nitridation rate strongly depends on the particle size and temperature. The smaller particle size exhibits the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In previous studies using the same starting material under the flow of nitrogen gas, 13), 14) a TiNSi 3 N 4 particulate composite was obtained, and 48.8 % of the reaction ratio without additives was achieved at 1,200°C. In this study, we obtained TiNSi 3 N 4 mixed powders with a fibrous Si 3 N 4 structure under the flow of NH 3 gas.…”
Section: Sio 2ðsþ þ Si ðSþ ! 2sio ðGþ ð7þmentioning
confidence: 84%
See 1 more Smart Citation
“…In previous studies using the same starting material under the flow of nitrogen gas, 13), 14) a TiNSi 3 N 4 particulate composite was obtained, and 48.8 % of the reaction ratio without additives was achieved at 1,200°C. In this study, we obtained TiNSi 3 N 4 mixed powders with a fibrous Si 3 N 4 structure under the flow of NH 3 gas.…”
Section: Sio 2ðsþ þ Si ðSþ ! 2sio ðGþ ð7þmentioning
confidence: 84%
“…Moreover, Maillé et al reported the influence of temperature, grain size, and holding time on the nitriding rate of TiSi 2 powder and identified chemical mechanisms at temperatures between 1,000 and 1,200°C for durations up to 50 h using a direct nitriding process under nitrogen gas flow. 13), 14) They did not, however, investigate the optimum conditions for achieving the highest percentage of reaction ratio without additives (a ratio of 48.8 % was achieved). The researchers also reported nitridation enhancement by the addition of nickel, 5) for which they achieved a 96.3 % reaction ratio.…”
Section: Introductionmentioning
confidence: 99%
“…During the first step, only TiN is formed and generates a layer that behaves as a diffusion barrier limiting silicon nitridation. The second step occurs after significantly longer exposures and involves a sluggish nitridation of silicon at the center of the TiSi2 grain thanks to the formation of opened porosities generated by the Kirkendall effect [29]. This mechanism slows down the progress of the reaction so that the nitridation kinetics are very low and the conversion is inadequate.…”
Section: Thermogravimetric Analysis and Reaction Mechanismmentioning
confidence: 99%
“…The exothermicity of this reaction and the formation of liquid silicon could be detrimental in the case of fibrous composites. In a previous work, we focused our attention on the nitridation of pure TiSi2 compacts at lower temperatures (1000-1200°C) to produce the matrix of a fibers-reinforced composite [29]. Accordingly to previous papers [30][31][32][33], it was found that the nitridation is sluggish in these conditions because of diffusional limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation